You are on page 1of 4

MATH 135 Midterm Solutions

1. Let A and B be mathematical statements.

(a) Complete the truth table below [4 marks]

A B (A = B) A = (B)
T T F F

T F T T

F T F T

F F F T

(b) Justify whether the compound statements (A = B) and A = (B) are logically equivalent.
[1 mark]
Soln. When A = F, B = T, we get that (A = B) is false, while A = (B) is true. Therefore the
statements are not logically equivalent.

2. Suppose a is an integer. Consider the following statement.


Statement 1. If 32 - ((a2 + 3)(a2 + 7)), then a is even.

Here is an incorrect proof of Statement 1. Determine the main flaw in the argument. [1 mark]
Attempted Proof. Suppose a is even. Then a2 is even, so both a2 + 3 and a2 + 7 are odd. Since 32 is even,
32 - ((a2 + 3)(a2 + 7)). 
Soln. This attempt assumes that the conclusion is true. We cannot prove an implication starting from the
conclusion.

3. For each of the statements given below, either prove that it is true or provide a counterexample to show
that the statement is false.

(a) For all integers a, b and c, if a | c and b | c then (a + b) | c. [3 marks]


Soln. The statement is false.
Consider a = 1, b = 2 and c = 4.
Then 1 | 4 and 2 | 4, but 1 + 2 = 3, which does not divide 4.

(b) For all integers a, b, c and d, if a | c and b | d, then ab | cd. [3 marks]


Soln. Since a | c, there exists k Z such that c = ak.
Since b | d, there exists l Z such that d = bl.
Multiply the two equations to get cd = akbl = ab(kl). Since k, l Z, kl Z. Therefore, ab | cd.

1
4. Suppose b is an integer. Consider the following implication about b.
Statement 2. If for all k N, b - k, then b = 0.

(a) State the hypothesis of Statement 2. [1 mark]


Soln. For all k N, b - k.
(b) State the conclusion of Statement 2. [1 mark]
Soln. b = 0.
(c) State the converse of Statement 2. [1 mark]
Soln. If b = 0, then for all k N, b - k.
(d) State the contrapositive of Statement 2. [2 marks]
Soln. If b , 0, then there exists k N such that b | k.
(e) State the negation of Statement 2 without using the word not or the symbol (but symbols such
as ,, -, etc. are fine). [2 marks]
Soln. For all k N, b - k and b , 0.
(f) Prove Statement 2. [2 marks]
Soln. Using the contrapositive.
Assume b , 0, and since b Z, |b| N.
Consider k = |b| in N.
If b < 0, then k = b. Otherwise, if b > 0, then k = b. In either case, b | k.
Therefore the contrapositive is true.
Hence Statement 2 must be true.
2n
P
5. Recall that for some n N, we may use the summation notation i to abbreviate the expression
i=n

n + (n + 1) + (n + 2) + + (2n 1) + 2n.

Complete the induction conclusion below to prove that for all n N, [3 marks]

2n
X 3 2 
i= n +n .
2
i=n

Proof. We will prove this statement by induction on n.


2
Base Case: When n = 1, on the left side, we have i = 1 + 2 = 3,
P
i=1
 
while on the right side, we have 3
2 (1)2 + 1 = 3
2 (2) = 3.
2  
i= 3
(1)2 + 1 is true.
P
Since the left and right side both equal 3, the property 2
i=1
Induction Hypothesis: Let k N. Assume that
2k
X 3 2 
i= k +k .
2
i=k

Induction Conclusion: When n = k + 1,

2
Soln. Starting from the left side,

2(k+1)
X
i = (k + 1) + (k + 2) + + (2k + 1) + (2k + 2)
i=k+1
= [k + (k + 1) + . . . + (2k)] + [(2k + 1) + (2k + 2) k]
2k
X
= i + (3k + 3)
i=k
3 2
  
= k + k + 3(k + 1) using induction hypothesis
2
3
= (k + 1)(k + 2) by factoring (k + 1)
2
3h i
= (k + 1)2 + (k + 1) ,
2
which is the right side of the required equation when n = k + 1.
Therefore, by the Principle of Mathematical Induction, we are done.


6. A sequence {an } is defined recursively by

a1 = 1, a2 = 4 and an = 2an1 an2 + 2 for n 3.

Prove that an = n2 for all n N. [6 marks]


Soln. Let P(n) : an = n2 . Use strong induction on n.
Base Cases: when n = 1, a1 = 1 = 12 , so P(1) is true.
When n = 2, a2 = 4 = 22 , so P(2) is also true.

Induction Hypothesis: Let k 2 be an integer. Assume for all 1 i k, P(i) is true.

Induction Conclusion: when n = k + 1, we have

ak+1 = 2ak ak1 + 2


= 2k2 (k 1)2 + 2 using induction hypothesis
= 2k2 k2 + 2k 1 + 2
= k2 + 2k + 1 = (k + 1)2 .

Thus, P(k + 1) is true.


By the Principle of Strong Induction, P(n) is true for all n N.

3
7. Suppose S and T are two sets. Recall the definition

T S = {x T : x < S} .

Prove that (S T) (T S) = . [3 marks]


Soln. Assume, for the sake of contradiction, that x (S T) (T S).
Therefore x S T and x T S. Since x S T, x S. On the other hand, since x T S, x < S
(contradiction).

8. Consider the following statement.


Statement 3. For all x, y R, if x < y then there exists z R such that x < z < y.

(a) Express the negation of Statement 3 without using the word not or the symbol. [2 marks]
Soln. There exists x, y R such that x < y and for all z R, x z or z y.
(b) Prove Statement 3. [4 marks]
Soln. Let x, y R. Assume x < y.
x+y
Consider z = 2 . Note that z R.
x+y
Now, x = 2x
2 = 2 < 2 = z.
x+x
x+y y+y
Similarly, z = 2 < 2 = y. Hence x < z < y.

9. Prove the following statement by contradiction. [3 marks]


Statement 4. For all integers n 3, if there exists k N such that n = k3 + 1, then n is not a prime.

[Hints: 1. n is a prime if and only if all the positive divisors of n are 1 and n itself.
2. k3 + 1 = (k + 1)(k2 k + 1).]
Soln. Let n 3 be an integer. Assume. for the sake of contradiction, that there exists k N such that
n = k3 + 1 and n is a prime.
By the given hint, we may write n = (k + 1)(k2 k + 1). Note that both k + 1 and k2 k + 1 must be positive
integers, and as n can be written as their product, therefore either k + 1 = 1, or k2 k + 1 = 1.
However, k + 1 , 1 as k 1. This means that k2 k + 1 = 1 must be true. Therefore, k2 k = 0, so either
k = 0 or k = 1. However, as k N, k = 0 is not possible, so k = 1. In that case, n = k3 + 1 = 13 + 1 = 2 < 3
(contradiction).

You might also like